Necrotizing Sialometaplasia Associated with Orthodontic Appliance: A Case Report - , Mariana Botelho Leite, Kaio Henrique Soares, Sâmia Francy Ferreira Alves, Lara Moreira Jalles Milani, Gabriela Ferreira Zanon Simões, Ana Terezinha Marques Mesquita (Archives of Current Research International, 2025)
Necrotizing Sialometaplasia (NS) is a rare, self-limiting inflammatory condition primarily affecting the minor salivary glands of the palate, accounting for less than 1% of salivary gland diseases. Trauma-induced ischemia and chemical irritation, particularly from gastric acid reflux, have been suggested as potential contributing factors. This study presents a case of NS in a 17-year-old female following the placement of a palatal breaker appliance, exploring its possible association with mechanical trauma and comparing it with existing literature.